Experimental research on a THGEM-based thermal neutron detector - 杨雷 周健荣 孙志嘉 张莹 黄朝强 孙光爱 王艳凤 杨桂妄 许虹 谢宇广 陈元柏 (Chinese physics C, 2015)
A new thermal neutron detector with a domestically produced THGEM （Thick Gas Electron Multiplier） was developed as an alternative to 3He to meet the needs of the next generation of neutron facilities. One type of Au-coated THGEM was designed specifically for neutron detection. A detector prototype has been developed and the preliminary experimental tests are presented, including the performance of the Au-coated THGEM working in At/CO2 gas mixtures and the neutron imaging test with 252 Cf source, which can provide the reference for experimental data for research in the future.